The Multifunctional Contribution of FGF Signaling to Cardiac Development, Homeostasis, Disease and Repair - Khosravi, Farhad; Ahmadvand, Negah; Bellusci, Saverio; Sauer, Heinrich (Frontiers in Cell and Developmental Biology, 2021)
The current focus on cardiovascular research reflects society's concerns regarding the alarming incidence of cardiac-related diseases and mortality in the industrialized world and, notably, an urgent need to combat them by more efficient therapies. To pursue these therapeutic approaches, a comprehensive understanding of the mechanism of action for multifunctional fibroblast growth factor (FGF) signaling in the biology of the heart is a matter of high importance. The roles of FGFs in heart development range from outflow tract formation to the proliferation of cardiomyocytes and the formation of heart chambers. In the context of cardiac regeneration, FGFs 1, 2, 9, 16, 19 and 21 mediate adaptive responses including restoration of cardiac contracting rate after myocardial infarction and reduction of myocardial infarct size. However, cardiac complications in human diseases are correlated with pathogenic effects of FGF ligands and/or FGF signaling impairment. FGFs 2 and 23 are involved in maladaptive responses such as cardiac hypertrophic, fibrotic responses and heart failure. Among FGFs with known causative (FGFs 2, 21 and 23) or protective (FGFs 2, 15/19, 16 and 21) roles in cardiac diseases, FGFs 15/19, 21 and 23 display diagnostic potential. The effective role of FGFs on the induction of progenitor stem cells to cardiac cells during development has been employed to boost the limited capacity of postnatal cardiac repair. To renew or replenish damaged cardiomyocytes, FGFs 1, 2, 10 and 16 were tested in (induced-) pluripotent stem cell-based approaches and for stimulation of cell cycle re-entry in adult cardiomyocytes. This review will shed light on the wide range of beneficiary and detrimental actions mediated by FGF ligands and their receptors in the heart, which may open new therapeutic avenues for ameliorating cardiac complications.